Proceedings of the 2011 2nd International congress on computer applications and computational science : Volume 1 - Nguyen, Quang Vinh; Gaol, Ford Lumban (Advances in Intelligent and Soft Computing, 2012)
The latest inventions in computer technology influence most of human daily activities. In the near future, there is tendency that all of aspect of human life will be dependent on computer applications. In manufacturing, robotics and automation have become vital for high quality products. In education, the model of teaching and learning is focusing more on electronic media than traditional ones. Issues related to energy savings and environment is becoming critical.   Computational Science should enhance the quality of human life,  not only solve their problems. Computational Science should help humans to make wise decisions by presenting choices and their possible consequences. Computational Science should help us make sense of observations, understand natural language, plan and reason with extensive background knowledge. Intelligence with wisdom is perhaps an ultimate goal for human-oriented science.   This book is a compilation of some recent research findings in computer application and computational science. This book provides state-of-the-art accounts in Computer Control and Robotics,  Computers in Education and Learning Technologies,  Computer Networks and Data Communications, Data Mining and Data Engineering,  Energy and Power Systems, Intelligent Systems and Autonomous Agents,  Internet and Web Systems, Scientific Computing and Modeling, Signal, Image and Multimedia Processing, and  Software Engineering.